“We” and the “others” as anthropological dimension and the modern idea of “national belonging”. Concluding thoughts - Contogeorgis, George (Social Cohesion and Development, 2024)
The main goal of this essay is to examine the concept of nation as the identity phenomenon par excellence in forming the image of oneself and, consequently, the image of the “other”. Hence, I will explore the political stake raised by this phenomenon in as much as it is at the origins of the emergence of a project for a cultural polysemy of collective identities with regards to the former monoculturalism and the emerging doctrine of multiculturalism